Flipped Classroom for Working Students: An Innovative Learning Model in Creative Writing - Probowati, Yeni (Corolla International Conference, 2025)
Numerous studies have demonstrated the educational and motivational advantages of using flipped classroom. On the other hand, research on teaching creative writing using flipped classroom is lacking for working students. The following gaps are intended to be filled by this paper: the need for a suitable framework for using flipped classroom to scaffold creative writing for working students. When compared to earlier times, students who work today have quite diverse traits, and as a result, their expectations have changed. As a result, using flipped classroom to pique students’ interest and enthusiasm in learning activities is quite challenging nowadays. Furthermore, using flipped classroom to solve specific teaching and learning issues is interesting. In this sense, modern educators are very interested in cutting-edge teaching strategies in creative writing that cater to the demands of the modern world and the needs of their students. The flipped classroom model is one of those innovative learning strategies.